Using convergence monitoring and damage mapping to interpret ground behaviour in Padcal Mine block caving - Monis, J.A.; Taban-ud, K.M. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Padcal Mine in the Philippines is one of the world’s longest-operating block caves, with more than 6 decades of continuous caving and multiple cave expansions. As the cave footprint has deepened and widened, increasing abutment loading, evolving cave geometry and uneven draw have produced complex deformation patterns and recurring damage to critical underground infrastructures. This paper presents a field-based approach for interpreting ground behaviour using convergence monitoring, systematic damage mapping, geological structural mapping and operational data from a mature block cave. Time-dependent convergence measurements from key haulage and production levels are analysed together with mapped damage, draw compliance and geological structures to identify whether ground movement is primarily stress-driven, draw-related or structure-controlled. The results show that convergence monitoring and damage mapping provide a reliable basis for managing ground stability in a mature, high-stress block cave, with clear value for other long-life caving operations worldwide.